A Custom Made Post and Core Technique for Restoring Badly Broken Mandibular Posterior Tooth: A Case Report - Guragain, Manjeev; Mathema, S.R.B.; Maharjan, S.K.; Sah, S. (Journal of Nepalese Prosthodontic Society, 2018)
The successful treatment of a badly broken tooth depends both on good endodontic therapy and prosthetic reconstruction of the tooth. Molars with almost total coronal destruction can be salvaged by the use of customized post and core. A number of methods have been suggested for making a cast post and core using two or more of the canals to increase retention of the prosthesis. This case report discusses a method to restore a structurally compromised, endodontically treated mandibular first molar using a customized cast post and core.